Accumulation of contaminants of emerging concern in food crops—part 1: Edible strawberries and lettuce grown in reclaimed water. (18th September 2015) - Hyland, Katherine C.; Blaine, Andrea C.; Dickenson, Eric R.V.; Higgins, Christopher P.
Abstract Contaminants of emerging concern present in domestic waste streams include a highly diverse group of potentially biologically active compounds that can be detected at trace levels in wastewater. Concerns about potential uptake into crops arise when reclaimed water is used in food crop production. The present study investigated how 9 contaminants of emerging concern in reclaimed water are taken up into edible portions of two food crops. Two flame retardant chemicals, tris(1‐chloro‐2‐propyl) phosphate (TCPP) and tris(2‐chloroethyl) phosphate (TCEP) and several polar pharmaceuticals (carbamazepine, diphenhydramine, sulfamethoxazole, and trimethoprim) accumulated in a linear, concentration‐dependent manner in lettuce (Lactuca sativa) irrigated with reclaimed water, suggesting passive uptake of both neutral and ionizable chemical contaminants in lettuce. Furthermore, concentration‐dependent accumulation of TCEP and TCPP from reclaimed water was also observed in strawberry fruits (Fragaria ananassa). Collectively, these data suggest that highly polar or charged contaminants can be taken up by crops from water bearing contaminants of emerging concern and can be accumulated in the edible portions. Using these data, however, estimates of human exposure to these contaminants from reclaimed water food crop accumulation suggest that exposure to the contaminants of emerging concern examined in the present study is likely substantially lower than current exposure guidelines. Environ Toxicol Chem 2015;34:2213–2221. © 2015 SETAC